Relationship between accounting benefits and ERP user satisfaction in the context of the fourth industrial revolution - NguyenThanh, Hung; Thanh Do, Minh; Trong Vu, Quang (International Journal of Scientific Research and Management (IJSRM), 2020)
In the context of 4th Industrial Revolution, the application of information technology to optimize business processes is more popular. Resource planning system (ERP) is applied by enterprises as an efficient solution to save costs and manage resources effectively. Besides, the application of ERP creates accounting benefits for end users. We conduct this study to determine the accounting benefits of ERP application. At the same time, we explore the relationship between these accounting benefit and user satisfaction. To achieve the aims of this research, the study employed empirical techniques like the Exploratory Factor Analysis (EFA) and Multiple Linear Regression. Research results show that a number of accounting benefits derived from the application of ERP that focus on the following four dimensions: operational, information technology, organizational, and management. The study provided evidence of the relationship between accounting benefits in terms of ERP application and user satisfaction as accountants.The study contributed to encourage Vietnamese enterprises to apply ERP to increase the value of accounting benefits. From there, these benefits contribute to providing timely and flexible information for management levels.